Effectiveness and tolerability of second‐line therapy with vildagliptin vs. other oral agents in type 2 diabetes: A real‐life worldwide observational study (EDGE). Issue 10 (21st August 2013) - Mathieu, C.; Barnett, A. H.; Brath, H.; Conget, I.; de, J. J.; Göke, R.; Márquez Rodriguez, E.; Nilsson, P. M.; Pagkalos, E.; Penfornis, A.; Schaper, N.C.; Wangnoo, S. K.; et al.
Summary Aim Real‐life studies are needed to confirm the clinical relevance of findings from randomised controlled trials (RCTs). This study aimed to assess the effectiveness and tolerability of vildagliptin add‐on vs. other oral antihyperglycaemic drugs (OADs) added to OAD monotherapy in a real‐life setting, and to explore the advantages and limitations of large‐scale 'pragmatic' trials. Methods EDGE was a prospective, 1‐year, worldwide, real‐life observational study in which 2957 physicians reported on the effects of second‐line OADs in 45, 868 patients with T2DM not reaching glycaemic targets with monotherapy. Physicians could add any OAD, and patients entered either vildagliptin or (pooled) comparator cohort. The primary effectiveness and tolerability end‐point (PEP) evaluated proportions of patients decreasing HbA1c > 0.3%, without hypoglycaemia, weight gain, peripheral oedema or gastrointestinal side effects. The most clinically relevant secondary end‐point (SEP 3) was attainment of end‐point HbA1c < 7% without hypoglycaemia or ≥ 3% increase in body weight. Results In this large group of T2DM patients, a second OAD was added at mean HbA1c of 8.2 ± 1.3%, with no baseline HbA1c difference between cohorts. Second‐line OAD therapy attained the PEP in the majority of patients, with higher attainment in those prescribed a vildagliptin‐based regimen. The adjusted odds ratio was 1.49 (95% CI: 1.42, 1.55; p < 0.001). In patients with baseline HbA1c ≥ 7%, SEP 3 was achieved by 35% of patients on a vildagliptin‐based combination and by 23% of those receiving comparator combinations. The adjusted odds ratio was 1.96 (95% CI: 1.85, 2.07; p < 0.001). Safety events were reported infrequently and safety profiles of vildagliptin and other OADs were consistent with previous data. Conclusion EDGE demonstrates that in a 'real‐life' setting, vildagliptin as second OAD can lower HbA1c to target without well‐recognised OAD side effects, more frequently than comparator OADs. In addition, EDGE illustrates that conducting large‐scale, prospective, real‐life studies poses challenges but yields valuable clinical information complementary to RCTs.